Variation in Vegetation Structure and Composition across Urban Green Space Types - Threlfall, Caragh G.; Ossola, Alessandro; Hahs, Amy K.; Williams, Nicholas S. G.; Wilson, Lee; Livesley, Stephen J. (Frontiers in Ecology and Evolution, 2016)
HIGHLIGHTS Vegetation structure and composition were measured in four major green space types Remnants and golf courses supported highest native plant richness Residential neighborhoods and urban parks supported highest exotic plant richness Residential neighborhoods lacked key habitat structures including old trees Green spaces can achieve complex vegetation with both native and exotic vegetation The ecological sustainability and function of urban landscapes is strongly influenced by the composition and structure of the local plant community. Taxonomic composition generally refers to the identity of the species comprising the community, while we define structure as the presence of multiple canopy layers, as well as stems of varying diameter and age. These aspects of urban vegetation significantly influence the ecology of cities, yet they are generally poorly quantified across the range of natural and constructed plant communities present in urban landscapes. We quantified vegetation composition and structure to (i) simultaneously assess their variation across four green spaces types (golf courses, public parks, residential neighborhoods, and patches of remnant vegetation) in Melbourne, Australia, and (ii) investigate the relationship between vegetation composition and structure within these green spaces. The four green space types supported distinctly different plant communities. Vegetation composition in the residential neighborhoods differed significantly from the others (p < 0.05), largely due to the increased richness of shrubs and cultivated plants, and the reduced presence of large trees. Residential neighborhoods had the highest plant species richness, although a large proportion of these species occurred infrequently. The structural complexity of understorey vegetation (calculated as % volume occupied) below 0.5 m was highest in remnant patches followed by golf courses, public parks, and residential neighborhoods. The structural complexity of understorey vegetation in remnant vegetation patches was very similar to that of golf courses even though some of the latter were dominated by exotic plant species. Variation in the composition and structure of urban vegetation might have great implications for the retention of faunal diversity within cities because different taxa have specific habitat requirements. Hence, further understanding of variations in the composition and structure of both natural and constructed plant communities in cities will greatly improve our ability to create urban landscapes that enhance both plant and animal biodiversity.